SITUS ASTANA GEDE KAWALI SEBAGAI SUMBER BELAJAR BAGI MAHASISWA SEJARAH - Ayu Septiani (Candrasangkala: Jurnal Pendidikan dan Sejarah, 2016)
This paper discusses the use of Situs Astana Gede Kawali as a source of learning. The elements discussed in this paper include the historicity Situs Astana Gede Kawali, the site as a source of learning history, learning strategies, and learning methods Situs Astana Gede Kawali as a source of learning. To discuss these elements used historical methods and descriptive method.